Intermittent Hypoxia-Induced Carotid Body Chemosensory Potentiation and Hypertension Are Critically Dependent on Peroxynitrite Formation. (20th December 2015) - Moya, Esteban A.; Arias, Paulina; Varela, Carlos; Oyarce, María P.; Del Rio, Rodrigo; Iturriaga, Rodrigo
Abstract : Oxidative stress is involved in the development of carotid body (CB) chemosensory potentiation and systemic hypertension induced by chronic intermittent hypoxia (CIH), the main feature of obstructive sleep apnea. We tested whether peroxynitrite (ONOO − ), a highly reactive nitrogen species, is involved in the enhanced CB oxygen chemosensitivity and the hypertension during CIH. Accordingly, we studied effects of Ebselen, an ONOO − scavenger, on 3-nitrotyrosine immunoreactivity (3-NT-ir) in the CB, the CB chemosensory discharge, and arterial blood pressure (BP) in rats exposed to CIH. Male Sprague-Dawley rats were exposed to CIH (5% O2, 12 times/h, 8 h/day) for 7 days. Ebselen (10 mg/kg/day) was administrated using osmotic minipumps and BP measured with radiotelemetry. Compared to the sham animals, CIH-treated rats showed increased 3-NT-ir within the CB, enhanced CB chemosensory responses to hypoxia, increased BP response to acute hypoxia, and hypertension. Rats treated with Ebselen and exposed to CIH displayed a significant reduction in 3-NT-ir levels (60.8 ± 14.9 versus 22.9 ± 4.2 a.u.), reduced CB chemosensory response to 5% O2 (266.5 ± 13.4 versus 168.6 ± 16.8 Hz), and decreased mean BP (116.9 ± 13.2 versus 82.1 ± 5.1 mmHg). Our results suggest that CIH-induced CB chemosensory potentiation and hypertension are critically dependent on ONOO − formation.